2020
DOI: 10.1080/21655979.2020.1860491
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 (ATF3) regulates cell growth, apoptosis, invasion and collagen synthesis in keloid fibroblast through transforming growth factor beta (TGF-beta)/SMAD signaling pathway

Abstract: 2021) Activating transcription factor 3 (ATF3) regulates cell growth, apoptosis, invasion and collagen synthesis in keloid fibroblast through transforming growth factor beta (TGF-beta)/SMAD signaling pathway,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
(40 reference statements)
0
38
0
Order By: Relevance
“…22 ATF3 induces the activation of TGF-β/Smad signalling pathway in keloid fibroblasts to accelerate growth and invasion, and suppress apoptosis of keloid fibroblasts. 23 Thus, these findings show that the TGFβ/Smad signalling pathway plays a crucial role in the formation of keloids. Additionally, a previous study has found that BMP4/Smad signalling pathway induces keloid myofibroblasts to differentiate into adipocytes, thereby inhibiting the formation of keloid.…”
Section: Discussionmentioning
confidence: 68%
“…22 ATF3 induces the activation of TGF-β/Smad signalling pathway in keloid fibroblasts to accelerate growth and invasion, and suppress apoptosis of keloid fibroblasts. 23 Thus, these findings show that the TGFβ/Smad signalling pathway plays a crucial role in the formation of keloids. Additionally, a previous study has found that BMP4/Smad signalling pathway induces keloid myofibroblasts to differentiate into adipocytes, thereby inhibiting the formation of keloid.…”
Section: Discussionmentioning
confidence: 68%
“…In the neuronal system, ATF3 plays a pro-survival role in ganglion cells and neurons [ 94 ]. Consistently, ATF3 protects against doxorubicin-induced apoptosis in cardiac myocytes [ 95 ] and stress-induced cell death in renal cells, β-cells [ 96 ], and keloid fibroblasts [ 97 ]. The collective evidence suggests that ATF3 plays a protective role in cell-stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Li believed that ATF3 expression in cardiac fibroblast could protect against heart failure, while ATF3 knockout markedly exaggerated hypertensive ventricular remodeling ( Li et al, 2017 ). Moreover, it is reported that ATF3 could also regulate cell growth, apoptosis, invasion, and collagen synthesis in keloid fibroblast through TGF-beta/SMAD signaling pathway ( Wang et al, 2021 ). In our study, we first verified that ATF3 overexpression could promote the proliferation, migration, and invasion of RA-FLS and MH7A ( Figures 8 , 9 ) and could stimulate those cells to secrete more pro-inflammation cytokines, like IL-1β, IL-6, and IL-8 ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%